Routine preoperative electrocardiogram in patients over 40 years of age: a hearty need or a customary practice? - Ghimire, A; Rahman, TR; Bhattarai, B; Koirala, S; Khatiwada, S; Dhital, D (Health Renaissance, 2011)
Background: Preoperative 12-lead electrocardiogram (ECG) can provide important information on the state of the patient’s myocardium and coronary circulation. Routine screening ECG preoperatively in all adult patients seems cumbersome and unnecessary. Objectives: To find out the incidence of ECG abnormality of patients above 40 years of age presenting in the preanaesthetic check up (PAC) clinic and to observe any associated co-morbid conditions. Methods: This is a prospective observational study done in the PAC clinic of the department of Anaesthesiology and Critical Care, at B. P. Koirala Institute of Health Sciences, Dharan from June2010 to August 2010 over a period 3 months. The study enrolled 360 patients aged 40 years and above. Laboratory investigations such as hemoglobin, blood grouping, urine routine and microscopic examinations along with biochemical parameters like blood urea, serum creatinine, fasting and post prandial blood sugar were reviewed. A 12-lead ECG was obtained for all patients included in the study. Results: Out of 360 patients, 168 were male and 192 female. Abnormal ECG was observed in 38 (10.5%) patients. Frequency of abnormal ECG increased with increasing age. Diabetic, hypertensive and smokers had higher incidence of abnormal ECG. Conclusion: A preoperative screening ECG for all adult patients aged 40 years visiting PAC clinic is relevant and desirable for risk- stratification. Keywords: abnormal ECG; preoperative evaluation; preanaesthetic check up; smoking habit; hypertension DOI: http://dx.doi.org/10.3126/hren.v9i2.4976 Health Renaissance 2011: Vol.9 (No.2): 73-77